Establishment and characterization of a radiation‐induced dermatitis rat model - Sheng, Xiaowu (J Cell Mol Med, 2019)
Radiation‐induced dermatitis is a common and serious side effect after radiotherapy. Current clinical treatments cannot efficiently or fully prevent the occurrence of post‐irradiation dermatitis, which remains a significant clinical problem. Resolving this challenge requires gaining a better understanding of the precise pathophysiology, which in turn requires establishment of a suitable animal model that mimics the clinical condition, and can also be used to investigate the mechanism and explore effective treatment options. In this study, a single dose of 90 Gy irradiation to rats resulted in ulceration, dermal thickening, inflammation, hair follicle loss, and sebaceous glands loss, indicating successful establishment of the model. Few hair follicle cells migrated to form epidermal cells, and both the severity of skin fibrosis and hydroxyproline levels increased with time post‐irradiation. Radiation damaged the mitochondria and induced both apoptosis and autophagy of the skin cells. Therefore, irradiation of 90 Gy can be used to successfully establish a rat model of radiation‐induced dermatitis. This model will be helpful for developing new treatments and gaining a better understanding of the pathological mechanism of radiation‐induced dermatitis. Specifically, our results suggest autophagy regulation as a potentially effective therapeutic target.